THE FATE OF DNA-CONTAINING PARTICLES PHAGOCYTIZED BY MAMMALIAN CELLS - Bensch, Klaus (The Rockefeller University Press, 1964)
Particulate DNA protein coacervates were digested immediately after being phagocytized by L strain fibroblasts in suspension culture. Enlargement of the phagocytotic vacuoles occurred simultaneously with a loss of the electron opacity of the phagocytized particles. Cytochemical reactions positive for non-specific esterase, acid phosphatase, and nucleoside phosphatase in the phagocytotic vacuoles provided additional evidence for the probability of complete hydrolysis of the phagocytized nucleoprotein.